Shear Performance of GFRP Reinforced Concrete Beams with Seawater and Chopped Fiber - Waleed Abdallah; Abdelrahman M. Farrag; Ahmed F. Deifalla; Amal. H. Ibrahim; Hamdy M. Mohamed; Ahmed H. Ali (Salehan Institute of Higher Education, 2023)
This paper reports an experimental study on the behavior and shear strength of concrete beams reinforced with longitudinal GFRP bars mixed with sea water. In order to evaluate how much concrete contributes to shear resistance, seven beams were tested in bending. Similar in size and concrete strength, the beams were longitudinally reinforced with glass fiber-reinforced polymer bars; however, they did not even have shear reinforcement. The beams, which measured 3,100 mm in length, 400 mm in depth, and 200 mm in width, were conducted and tested up to failure. The test variables were longitudinal reinforcement ratios (1.0, 1.4, and 2.0%), chopped fiber content (0, 0.5, 2, and 3 kg/m3), and mixing water type (freshwater and seawater). The test findings showed that increasing the reinforcement ratio increased the neutral-axis depth and allowed the formation of more closely spaced fractures while decreasing the loss of flexural stiffness after cracking. By increasing the area of concrete in compression, this in turn enhances the contribution of aggregate interlock as well as the contribution of uncracked concrete. Furthermore, increasing the reinforcement ratio improves the dowel action, which reduces the tensile stresses that are created in the concrete around it. Doi: 10.28991/CEJ-2023-09-04-05 Full Text: PDF